THE ROLE OF FISCAL POLICY IN THE CRISIS: A LITERATURE REVIEW - Siallagan, Windraty (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
Global crisis due to Corona Virus Disease (COVID) 19 pandemic motivates research concerning the role of fiscal policy in the crisis. Lessons learned on success dan failed factor of fiscal in responding crisis is of greater importance. This research employs review literature to identify the current status of literature on the role of fiscal in crisis.  The research aims to review previous research, mainly literature on a fiscal policy designed during an economic recession or crisis. Lessons from the past crisis and the extent to which fiscal policy has roles in overcoming crisis are evaluated through literature.  By investigating and analyzing 29 academic works of literature, this research finds that fiscal stimulus and austerity measures are two government options in a crisis.  When the fiscal stimulus is launched, the deficit becomes the following consequence, usually funded by debt. This research also shows a plethora of studies on the fiscal role in developed countries such as Europe, but only a meager of research conducted in Asia, particularly South-Eastern Asia. The finding encourages research on the extension of fiscal role themes in crisis and mixed-method employment to render new insights into the subject matter. gb777